A Review of the Cardiovascular Consequences of Concussion and Mild Traumatic Brain Injury - Avdeev, William (British Journal of Healthcare and Medical Research, 2024)
Objection: During 2010-2016, approximately 2.7 million annual emergency department visits for sport injuries were made by patients ages 5 to 24 years old. Injuries in professional sports have been reported as high as 49.4 per 1000 athletes in ice hockey, 64.7 in football, 19.3 in basketball and 3.61 in baseball. Sports-related injuries, specifically concussions, have healthcare costs as well as long-term physical and psychological implications. As the result, sports medicine professionals and organizations have attempted to implement injury risk reduction strategies and promote safe sport participation. Methods: This study examines several existing studies of concussion injuries and their impact on cardio-vascular health and draws conclusions and recommendations based on their review. Literature search was conducted using ABI Business Periodicals Database. Three studies were examined, and conclusions were drawn based on their findings. In addition, based on the findings in the published studies, inferences were drawn for further research and examination. Results: Athletes with concussion history display suppressed cardiac autonomic recovery after moderate aerobic exercise, compared to those who did not suffer any concussion injuries. Players with multiple previous concussions displayed increased time to physiological recovery after moderate exercise compared to athletes with only one or no concussions. Conclusion: This paper will discuss the need to respond to these statistics. Further studies are needed to examine the long-term effect of concussion injuries, where social and economic impacts also cannot be overlooked.